Estimativa da geração de biogás no aterro Sanitário metropolitano de João Pessoa através Do teste BMP - Silva, Gardênia Azevedo (2012)
The study of biological conversion for energy purposes in landfills of municipal solid waste is a major breakthrough to the society and it is considered having an extremely environmental and economic importance. Given this ostentation a study was conducted in the João Pessoa's metropolitan landfill , in order to estimate the production of biogas and its main component, methane. There is no an official protocol of the Biochemical Methane Potential Test (BMP) for the prediction of gas generated for this reason literature searches were conducted and a methodology was adapted based on the characterization and monitoring of the main factors involved in the degradation process. The steps of the study were as following: waste's gravimetric characterization, physicochemical characterization and acclimatization of inoculum and the BMP test, which includes the inoculation of the reaction ways , the monitoring of the biogas' volume produced, the quantitative and qualitative control of the generation of gases comprising the biogas and consequently the estimate of the generation of biogas in the landfill. The results has showed that the gravimetric characterization of the municipal solid waste, which used the French method MODECOM brought data definitions more precise, giving reliability to the composition of the waste. The proposed methodology for the BMP test was effective in obtaining the results, as it has produced a volume of accumulated biogas 282.66 NL.kg-1MS in 90 days in the biodegradable waste, consistent with the literature, providing a favorable production of biogas in the João Pessoa's metropolitan landfill. As it was considered an excellent experimental tool for determining the potential for the biogas generation in MSW, the BMP test enables the preparation for the official procedure.